Improvement connection control of optical components using TV means - Божко, Костянтин Михайлович; Сидоренко, Сергій Юрійович; Кущовий, Сергій Миколайович (Technology audit and production reserves, 2015)
The possibility of using the TV means for control of the nodes and optical components, in particular, the presence of defects in their joints. The necessity to control the optical components during the manufacturing process throughout the process flow as it provides a saving of material and financial resources is proved. It is proved that TV is a preferred method and means to interference and shadow method in the control of optical components and their joints. An overview of joining technology of optical components is done and their requirements on permissible size and number of defects per unit area of the connection are classified. It is theoretically proved the possibility of measurement of geometrical sizes of defects with an accuracy which exceeds the minimum element resulting in a television camera image – one pixel. Subpixel measurements are provided by algorithmic methods with computer imaging. The properties of the error sources of television measurement and the criteria for neglecting some of them are analyzed. In particular, the possibility of compensating unevenness sensitivity of television camera is marked. The study shows the need and opportunity to use a wide television methods and means for controlling optical defects in the components, as well as compounds that lead to substantial savings in the production process, and the operation of optical devices and systems.